2011
DOI: 10.1007/s00109-010-0717-z
|View full text |Cite
|
Sign up to set email alerts
|

Rad is a p53 direct transcriptional target that inhibits cell migration and is frequently silenced in lung carcinoma cells

Abstract: The p53 tumor suppressor exerts its function mainly as a transcriptional activator. Here we show that the Ras-related small GTPase Rad, an inhibitor of Rho kinase, is a direct transcriptional target of p53. Expression of Rad messenger RNA (mRNA) and protein was induced by DNA damage in a p53-dependent manner. The -2934/-2905-bp Rad promoter region, to which p53 bound, was required for p53-mediated Rad gene activation. Treatment by DNA damaging agents increased p53 occupancy and histone acetylation in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…The fact that the Ras mutation is found only in a certain subset of ovarian cancers (53) and ϳ30% of other human cancers (1, 2) suggested that Ras mutation was not the only cause for RRAD epigenetic inactivation in cancer. Indeed, Hsiao et al recently demonstrated that RRAD was a direct transcriptional target of p53 and that activation of p53 leads to up-regulation of RRAD (25). Considering the fact that p53 is frequently mutated in cancer cells, we speculate that loss of p53 function is another cause for RRAD down-regulation in tumor tissues.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The fact that the Ras mutation is found only in a certain subset of ovarian cancers (53) and ϳ30% of other human cancers (1, 2) suggested that Ras mutation was not the only cause for RRAD epigenetic inactivation in cancer. Indeed, Hsiao et al recently demonstrated that RRAD was a direct transcriptional target of p53 and that activation of p53 leads to up-regulation of RRAD (25). Considering the fact that p53 is frequently mutated in cancer cells, we speculate that loss of p53 function is another cause for RRAD down-regulation in tumor tissues.…”
Section: Discussionmentioning
confidence: 76%
“…6, D-F). Considering that RRAD inhibited cell migration in vascular smooth muscle cells (51) and lung cancers (25) and that disruption of RRAD resulted in cell cycle arrest and senescence (20,52), we propose that RRAD is a tumor suppressor gene, which may be a potential new anti-tumor target through regulating RRAD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bax activation occurs in response to a variety of apoptotic stimuli, and the p53 directly regulates Bax expression and induces apoptosis via the mitochondrial pathway. Rad, a Rho kinase inhibitor, suppressed p53-mediated cell migration in lung cancer [40]. Rho A and ROCK activation is associated with cell migration due to the mutation or loss of p53 [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…As important epigenetic modification manners, histone methylation and DNA methylation directly regulate numerous cancer-related genes expression [20][21][22][23]. Aberrant histone methylation and DNA methylation, mediated by histone methyltransferase and DNA methyltransferase, respectively, have been found in many types of cancers [24,25].…”
Section: Introductionmentioning
confidence: 99%